Abstract Introduction of a Novel Pathogenic Variant (c.1684G>A) in The SOX5 Gene Associated With Lamb–Shaffer Syndrome in a Family From North of Iran - Akbar Amirfiroozy; Hossein Jalali; Atefeh Khoshaeen; Mohammad Reza Mahdavi; Mahan Mahdavi (Case Reports in Clinical Practice, 2024)
So far, different types of SOX5 variants have been reported in patients with LAMSHF syndrome, which are mainly clustered in the HMG domain. The LAMSHF syndrome has a broad variety of clinical manifestations such as developmental delay, speech delay, intellectual disability, and behavioral disturbances. In this article, we aim to present three cases with Lamb–Shaffer syndrome who are heterozygotes for a novel variant (c.1684G>A) in the SOX5 gene in a family from the north of Iran.A 38-year-old male case with moderate mental retardation and strabismus, with a head circumference size of 56 cm, was tested for genetic diagnosis. The results of whole- exome sequencing (WES) indicated the c.1684G>A pathogenic variant (NM_006940.6) in the SOX5 gene in a heterozygote state. Family analysis showed that the proband’s sister and father, who have similar symptoms, also carry the detected variant.Like the previous cases, the presented cases with a missense variant in the HMG- domain also have a mild phenotype. The introduction of new patients, especially with new pathogenic variants, is fundamental to increasing our knowledge about the disease and possible genotype–phenotype correlations.